The synergistic effects of cationic surfactant and smart seawater on the recovery of medium-viscosity crude oil from low-permeability carbonates - Osama Massarweh (17012217) (2023)
In the petroleum industry, there is a continuous search for cost-effective enhanced oil recovery (EOR) methods to increase oil extraction. Surfactant-based EOR is one of these effective methods, which is applied after the primary and secondary recovery phases. This paper presents an experimental study on the use of a cationic surfactant, hexadecyltrimethylammonium bromide (CTAB, CH3(CH2)15N(Br)(CH3)3), and smart seawater (SW) for EOR in low-permeability carbonate rock with medium viscosity crude oil. Smart SW was prepared by modifying the concentrations of Ca2+, Mg2+, and SO42- in synthetic offshore SW. The aqueous stability of CTAB was tested in different salinities of smart SW at the reservoir temperature. It was demonstrated that CTAB is stable at 55 °C, which was further confirmed through optical transmittance measurements, revealing values mostly exceeding 93%. The use of smart SW and CTAB significantly altered the wettability of carbonate rock towards water-wet and reduced the interfacial tension (IFT) between crude oil and water, reaching levels below 0.087 mN/m. However, the presence of smart SW increased the adsorption of CTAB onto the surface of carbonate rock. Nevertheless, the adsorption values were significantly below 1 mg/g-rock. Smart SW + CTAB resulted in a total oil recovery of 76.71% of original oil-in-place (OOIP), compared to 71.70% of OOIP with unmodified SW + CTAB. These results suggest that the use of smart SW in combination with CTAB is a promising approach for enhancing the recovery of medium-viscosity oil from tight carbonate reservoirs. Findings from this study can help in better understanding the optimal conditions for the application of smart SW-CTAB flooding to improve the effectiveness of tertiary recovery operations in the upstream oil sector. Other Information Published in: Journal of Molecular Liquids License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.molliq.2023.122866